AB0805 WHAT FACTORS AFFECT THE RESULT OF LONG-TERM ANALGESIC THERAPY FOR OSTEOARTHRITIS? DATA FROM A MULTICENTER OPEN STUDY OF ORAL AVOCADO/SOYBEAN UNSAPONFABLES EFFECTIVENESS. (June 2019) - Pogozheva, Elena; Karateev, Andrey; Lila, Alexander; Amirdzhanova, Vera; Filatova, Ekaterina
Abstract : Background: Symptomatic slow-acting drugs for OA (SYSADOAs) and oral nonsteroidal anti-inflammatory drugs (NSAIDs ) play a central role in the pharmacological management of osteoarthritis (OA). Factors affecting the effectiveness of OA therapy should be taken into account. Objectives: to identify factors affecting the effectiveness of long-term analgesic therapy in patients with OA. Methods: the study included 6448 patients with knee OA (mean age 57.8 ± 10.2 years, 70, 9% women), with pain level ≥40 mm VAS. All patients received oral avocado/soybean unsaponfables (ASU) 300 mg/day within 3 months and ketoprofen lysine salt (KLS) 320 mg/day within 2 weeks at the beginning of the study. A 100 mm visual analog scale (VAS) was used to assess pain intensity. The result of treatment was evaluated on a scale of 0-5 points, where 0 – no effect, 5 - excellent effect. The criteria for a "good response" to therapy were: pain reduction ≥50% and treatment result ≥ 4 points. The value of the studied factors was determined using odds ratio; 95% confidence interval (OR; 95% CI). Results: After 3 months of therapy the pain level decreased from 63.7 ± 12.0 mm to 14.2 ± 11.7 mm. A good response to treatment was noted in 87.4% of patients. Sex, body mass index ≥ 30 kg/m 2, type 2 diabetes, poor effect of NSAIDs and SYSADOAs in history did not affect the result. The effectiveness of treatment was less in patients >65 years (OR 0.418; 95% CI 0.342-0.509, p<0.001), OA stage ≥ 2 by Kelgren-Lawrence (OR 0.556; 95% CI 0.298-0.738, p<0.001), with rest pain (OR 0.690; 95% CI 0.596 - 0.800, p<0.001), synovitis (OR 0.780; 95% CI 0.673-0.900, p=0.001), and sensory symptoms such as burning, pain cold, electric shocks (OR 0.530; 95% CI 0.458-0.613, p<0.001). Conclusion: the ASU and KLS combination allows to achieve successful pain control in OA. A number of factors: age >65 years, OA stage ≥ 2 by Kelgren-Lawrence, rest pain, synovitis, and sensory symptoms are associated with the worst result of treatment. Disclosure of Interests: Elena Pogozheva: None declared, Andrey Karateev: None declared, Alexander Lila Speakers bureau: Pfizer, Inc., MSD, Novartis, AbbVie Inc., Celgen Corporation, Biocad, Janssen, UCB, Inc., Vera Amirdzhanova: None declared, Ekaterina Filatova: None declared